The Homeostasis of Iron, Copper, and Zinc in Paracoccidioides Brasiliensis, Cryptococcus Neoformans Var. Grubii, and Cryptococcus Gattii: A Comparative Analysis - Silva, Mirelle G.; Schrank, Augusto; Bailão, Elisa Flávia L.; Bailão, Alexandre M.; Borges, Clayton L.; Staats, Charley C.; Parente, Juliana A.; Pereira, Maristela; Salem-Izacc, Silvia M.; Mendes-Giannini, Maria José S.; Zancopé-Oliveira, Rosely M.; Rosa E Silva, Lívia K.; et al. (Frontiers in Microbiology, 2011)
Iron, copper and zinc are essential for all living organisms. Moreover, the homeostasis of these metals is vital to microorganisms during pathogenic interactions with a host. Most pathogens have developed specific mechanisms for the uptake of micronutrients from their hosts in order to counteract the low availability of essential ions in infected tissues. We report here an analysis of genes potentially involved in iron, copper and zinc uptake and homeostasis in the fungal pathogens Paracoccidioides brasiliensis, Cryptococcus neoformans var. grubii and Cryptococcus gattii. Although prior studies have identified certain aspects of metal regulation in Cryptococcus species, little is known regarding the regulation of these elements in P. brasiliensis. We also present amino acid sequences analyses of deduced proteins in order to examine possible conserved domains. The genomic data reveals, for the first time, genes associated to iron, copper and zinc assimilation and homeostasis in P. brasiliensis. Furthermore, analyses of the three fungal species identified homologues to genes associated with high-affinity uptake systems, vacuolar and mitochondrial iron storage, copper uptake and reduction, and zinc assimilation. However, homologues to genes involved in siderophore production were only found in P. brasiliensis. Interestingly, in silico analysis of the genomes of P. brasiliensis Pb01, Pb03 and Pb18 revealed significant differences in the presence and/or number of genes involved in metal homeostasis, such as in genes related to iron reduction and oxidation. The broad analyses of the genomes of P. brasiliensis, Cryptococcus neoformans var. grubii and Cryptococcus gattii for genes involved in metal homeostasis provide important groundwork for numerous interesting future areas of investigation that are required in order to validate and explore the function of the identified genes and gene pathways.